1984
DOI: 10.1017/s0025315400059610
|View full text |Cite
|
Sign up to set email alerts
|

The Life Cycle and Population Dynamics of Idotea Pelagica and I. Granulosa (Isopoda: Valvifera) In South-East Ireland

Abstract: Populations of Idotea pelagica and Idotea granulosa were studied monthly at Carnsore Point, County Wexford, from July 1978 to October 1979. The density of I. pelagica in mussel beds varied between 26 and 180/100 cm, reaching a peak in June. Numbers of I. granulosa in samples of Gigartina stellata fluctuated from month to month and averaged 200/100 g dry weight of algae. Peak densities were recorded in September of both years. Both species exhibited continuous growth, and breeding occurred throughout the year b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…In C. isopus, guarding males were always larger than females, and there was no correlation in body length between guarding males and guarded females (Fig. 6) indicating non sizeassortative mating; a similar trend was also reported in I. pelagica (Healy & O'Neill, 1984).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…In C. isopus, guarding males were always larger than females, and there was no correlation in body length between guarding males and guarded females (Fig. 6) indicating non sizeassortative mating; a similar trend was also reported in I. pelagica (Healy & O'Neill, 1984).…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, the lowest water temperature (3°C) matched the lowest water temperature of the Baltic Sea (Salemaa, 1979). Healy & O'Neill (1984) have shown that low temperature is critical for isopods and their activity drops when the water temperature falls below 6°C. Therefore the defined breeding periods of isopods living in the Baltic Sea and Hakodate Bay are likely caused by low temperature which suppresses growth and breeding.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations